Pengaruh Gaya Kpemimpinan dan Komunikasi terhadap Kinerja Karyawan pada Hotel Gajahmada Graha Malang - Dewi Ratnawati; Sri Wilujeng; Arien Anjar Puspitosari Suharso (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
This study aims to analyze the influence of leadership and communication styles on employee performance at the Gajahmada Graha Hotel in Malang. This type of research is the distribution of questionnaires. The population in this study were all employees of the Hotel Gajahmada Graha Malang as many as 56 employees. The sampling technique used in this study was a saturated sampling technique, which is determining the number of samples from all population members, namely 56 employees. The analytical tool used is multiple linear regression analysis. The results of the study concluded that: (1) Leadership style does not have a positive and significant effect on employee performance, (2) Communication has a positive and significant effect on employee performance, (3) Simultaneously together leadership and communication styles have a significant effect on employee performance. Keywords: Employee performance, Leadership Style, Communication